THE ROLE OF INFORMATION AGENCIES IN MODERN MASS MEDIA - M. G. Madera (Дискурс, 2018)
Modern political sociology covers in detail the issues of formation of public opinion in the traditional media - TV, press, and radio. But the problem of direct influence of informational agencies on target audience remains fairly undeveloped. The role of information agencies in mass communication has undergone a number of changes over the previous two decades. The dynamics and nature of these changes are identified in the framework of this article. Thanks to the progress of science and technology, news agencies, bypassing the media, have become able to establish links with the end consumer of the news. Researchers are required to "reassemble links" of the classical communication model: the source of information - the message - the transmitting channel (news agency) - the information interpreter (media) - the recipients of the message (the audience).